Increases in plastic bottles washing ashore on sub-Antarctic Marion Island - Peter G. Ryan; Azwianewi B. Makhado; Thando Cebekhulu; Robert J.M. Crawford; Bruce M. Dyer; Makhudu J. Masotla; Vonica Perold; Maelle Connan (Marine Pollution Bulletin, 2026)

Long-term changes in the incidence and characteristics of plastic ingested by White-chinned Petrels - Abigail Campbell; Vonica Perold; Peter G. Ryan (Marine Pollution Bulletin, 2025)

Long-term variations in size and polymer type of meso- and microplastics in seabirds and on beaches since the 1980s - Vonica Perold; Coleen L. Moloney; Peter G. Ryan (Environmental Pollution, 2025)

Little change in plastic loads in South Atlantic seabirds since the 1980s - Vonica Perold; Robert A. Ronconi; Coleen L. Moloney; Ben J. Dilley; Maëlle Connan; Peter G. Ryan (Science of The Total Environment, 2024)

Regurgitated skua pellets containing the remains of South Atlantic seabirds can be used as biomonitors of small buoyant plastics at sea - Vonica Perold; Maëlle Connan; Giuseppe Suaria; Eleanor A. Weideman; Ben J. Dilley; Peter G. Ryan (Marine Pollution Bulletin, 2024)

First evidence of mouse predation killing adult great albatrosses - Maëlle Connan; Christopher W. Jones; Michelle M. Risi; Lucy K. Smyth; Steffen Oppel; Vonica Perold; Kim L. Stevens; Roelf Daling; Peter G. Ryan (Biological Invasions, 2024)
Invasive rodents threaten native species in numerous ecosystems, especially oceanic islands. The House Mouse Mus musculus is the only introduced mammal species on sub-Antarctic Gough and Marion Islands. Ample evidence exists of mice preying upon seabird chicks on these two islands, but there have been only a few reports of attacks on adult seabirds, none of which has been fatal. We report the first deaths of adult great albatrosses due to mouse attacks. On Gough Island, three Tristan Albatrosses Diomedea dabbenena (Critically Endangered) brooding small chicks were observed with wounds typical of mouse attacks in March–April 2021; two likely abandoned their chick, causing breeding failure, and the third was found dead eight days after discovery with large blowfly larvae in the wound. On Marion Island, two wounded and eight dead adult Wandering Albatrosses D. exulans (Vulnerable) were found in April 2023. Inspection of the wounded individuals, as well as the injuries on the fresh carcasses strongly suggest that mouse predation was the cause of death. Gough Island is home to virtually all Tristan Albatrosses, and Marion Island is the single most important breeding site for Wandering Albatrosses, home to about a quarter of all breeding birds. The death of breeding adults of these long-lived species emphasizes the urgent need to eradicate introduced mice from these islands.

Abundance and composition of small floating plastics in the eastern and southern sectors of the Atlantic Ocean - Giuseppe Suaria; Paolo Cappa; Vonica Perold; Stefano Aliani; Peter G. Ryan (Marine Pollution Bulletin, 2023)

Proximity to coast and major rivers influence the density of floating microplastics and other litter in east African coastal waters - Eleanor A. Weideman; Vonica Perold; Vincenzo Donnarumma; Giuseppe Suaria; Peter G. Ryan (Marine Pollution Bulletin, 2023)

Birds of a Feather Eat Plastic Together: High Levels of Plastic Ingestion in Great Shearwater Adults and Juveniles Across Their Annual Migratory Cycle - Anna R. Robuck; Christine A. Hudak; Lindsay Agvent; Gwenyth Emery; Peter G. Ryan; Vonica Perold; Kevin D. Powers; Johanna Pedersen; Michael A. Thompson; Justin J. Suca; Michael J. Moore; Craig A. Harms; et al. (Frontiers in Marine Science, 2022)
Limited work to date has examined plastic ingestion in highly migratory seabirds like Great Shearwaters ( Ardenna gravis ) across their entire migratory range. We examined 217 Great Shearwaters obtained from 2008–2019 at multiple locations spanning their yearly migration cycle across the Northwest and South Atlantic to assess accumulation of ingested plastic as well as trends over time and between locations. A total of 2328 plastic fragments were documented in the ventriculus portion of the gastrointestinal tract, with an average of 9 plastic fragments per bird. The mass, count, and frequency of plastic occurrence (FO) varied by location, with higher plastic burdens but lower FO in South Atlantic adults and chicks from the breeding colonies. No fragments of the same size or morphology were found in the primary forage fish prey, the Sand Lance ( Ammodytes spp., n = 202) that supports Great Shearwaters in Massachusetts Bay, United States, suggesting the birds directly ingest the bulk of their plastic loads rather than accumulating via trophic transfer. Fourier-transform infrared spectroscopy indicated that low- and high-density polyethylene were the most common polymers ingested, within all years and locations. Individuals from the South Atlantic contained a higher proportion of larger plastic items and fragments compared to analogous life stages in the NW Atlantic, possibly due to increased use of remote, pelagic areas subject to reduced inputs of smaller, more diverse, and potentially less buoyant plastics found adjacent to coastal margins. Different signatures of polymer type, size, and category between similar life stages at different locations suggests rapid turnover of ingested plastics commensurate with migratory stage and location, though more empirical evidence is needed to ground-truth this hypothesis. This work is the first to comprehensively measure the accumulation of ingested plastics by Great Shearwaters over the last decade and across multiple locations spanning their yearly trans-equatorial migration cycle and underscores their utility as sentinels of plastic pollution in Atlantic ecosystems.

Toward Balancing the Budget: Surface Macro-Plastics Dominate the Mass of Particulate Pollution Stranded on Beaches - Peter G. Ryan; Eleanor A. Weideman; Vonica Perold; Coleen L. Moloney (Frontiers in Marine Science, 2020)